Spies and holy wars : the Middle East in 20th-century crime fiction - Simon, Reeva S. (University of Texas Press, 2010)
"For anyone who has a taste for either spy novels or the presentation of Middle Easterners in popular culture, this is a fascinating read."--Richard Bulliet, Professor of History, Columbia University